1993
DOI: 10.1002/hep.1840170519
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cyclic AMP response element in rat fibronectin gene expression

Abstract: Fibronectin expression is of considerable importance in normal and fibrotic liver. Plasma fibronectin levels are correlated with good prognosis in liver failure, and cellular fibronectin plays a crucial role in fibrogenesis. In this study, we observed that the H4II rat hepatoma cell line does not express fibronectin. Furthermore, a recombinant vector (pFGH) containing the promoter elements of the fibronectin gene showed no promoter function when transfected into this cell line. However, pFGH was actively expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Although CRE is not the cis-element for Taxinducibility of the FN gene, it may be important in the basal expression of the FN gene because CRE deletion significantly decreased the basal activity of the reporter gene. This is well consistent with the previous study that CRE is indispensable for the constitutive expression of the FN gene (31).…”
Section: Discussionsupporting
confidence: 94%
“…Although CRE is not the cis-element for Taxinducibility of the FN gene, it may be important in the basal expression of the FN gene because CRE deletion significantly decreased the basal activity of the reporter gene. This is well consistent with the previous study that CRE is indispensable for the constitutive expression of the FN gene (31).…”
Section: Discussionsupporting
confidence: 94%
“…the presence of an important regulatory element for the basal activity within the sequence from Ϫ166 to Ϫ123. In support of these results, a previous study reported that the sequence between Ϫ164 and Ϫ90 is important for the basal expression of the rat FN gene and this activity is mediated by CRE at Ϫ160 [Miao et al, 1993]. Further deletion to Ϫ69 decreased the basal promoter activity by 90% relative to that of pGL2F1900 ( Fig.…”
Section: Identification Of the Pma-responsive Region In The Fn Promotersupporting
confidence: 77%
“…Regulatory elements and transcription factors responsible for the regulation of the FN gene expression by the cyclic AMP pathway and several factors have been described . Cyclic AMP-responsive elements (CRE) at position Ϫ160 and Ϫ170 of the rat and human FN promoter, respectively, have been shown to mediate the basal and cAMP-induced expression of the FN gene [Bowlus et al, 1991;Miao et al, 1993]. Among many CRE-binding proteins described, ATF-2 binds to the CRE of the human FN gene and cooperates with NF-1 and CP1 that bind to an adjacent CCAAT element for the transcription of the FN gene in hepatocytes [Srebrow et al, 1993;Alonso et al, 1996].…”
mentioning
confidence: 99%
“…*P < 0.05 keloid ®broblasts (Sible et al 1996). Evaluation of transcriptional regulatory elements of the FN gene in rat skin ®broblasts by mutational studies resulted in mutagenesis of the sequence between )164 and )90 which exhibits homology to the consensus binding site for CRE (Miao et al 1993). On the other hand, in adenovirus E1-transformed rat cells, the nuclear factor G10BP binding to the G10 stretch from positions )239 to )230 and two GC boxes consisting of the G10 stretch with one internal C residue insertion from positions )105 to )95 and )54 to )44, showed the strongest repressive activity (Nakamura et al 1992).…”
Section: Discussionmentioning
confidence: 99%